SYSTEMATIC LITERATURE REVIEW : ANALISIS SISTEMATIS PERAN INFRASTRUKTUR NIRKABEL DALAM TRANSFORMASI EKOSISTEM MOBILE COMMERCE - Al Faisal, Aldy; Veri, Jonh (Jurnal Ekonomi Bisnis Kompetif, 2025)
ecosystem. This study aims to systematically analyze the role of wireless infrastructure in the transformation of the mobile commerce ecosystem using a Systematic Literature Review (SLR) approach. Of the 200 articles obtained, 5 articles met the inclusion criteria and were further analyzed. The rapid development of wireless technology has become a major catalyst in the transformation of the mobile commerce (m-commerce) ecosystem, enabling faster, safer, and more personalized digital transactions. Wireless infrastructure such as 4G, 5G, Wi-Fi, and Internet of Things (IoT) networks play a central role in supporting high connectivity, low latency, and scalability of m-commerce services. However, a comprehensive understanding of the contribution of this infrastructure in a global context remains fragmented. This study presents a systematic literature review (SLR) to analyze the role of wireless infrastructure in the evolution of the m-commerce ecosystem, based on a synthesis of 5 leading scientific studies from 2020 to 2025 drawn from the Scopus database. Through a PRISMA-based methodological approach, this study identifies three main themes: (1) the impact of wireless technology on performance and user experience, (2) implementation challenges including cybersecurity, digital disparity, and infrastructure costs, and (3) integration trends with supporting technologies such as edge computing, AI, and digital payments. The results show that 5G and Wi-Fi 6 are key drivers of m-commerce innovation, particularly in real-time applications such as mobile payments, augmented reality (AR) shopping, and smart logistics. The study also uncovers gaps in infrastructure access in developing regions that hinder digital inclusion. The findings from this SLR provide a conceptual foundation for researchers, technology developers, and policymakers in designing strategies for developing a more inclusive, secure, and sustainable m-commerce ecosystem in the era of high connectivity.